IMPLEMENTASI GOOD CORPORATE GOVERNANCE LEMBAGA AMIL ZAKAT YAYASAN DOMPET UMMAT KALIMANTAN BARAT - Tashadi Tarmizi; Soraya, Soraya; Risti Rahmaniar (Jurnal Cakrawala Ilmiah, 2025)
Zakat is an obligation for Muslims which must be managed institutionally in accordance with Islamic law. The Amil Zakat Institution (LAZ) has the task of assisting the collection, distribution and utilization of zakat and must have good governance and the ability to manage finances. This study aims to identify and analyze the implementation of the principles of Good Corporate Governance. The object of research is the Amil Zakat Institute (LAZ) of the Dompet Ummat Foundation of West Kalimantan. The research method uses qualitative methods with interviews and documentation as data collection tools. The results of the study show that from the principles of Good Corporate Governance the Amil Zakat Institute (LAZ) Dompet Ummat Foundation, West Kalimantan, has implemented the principles of transparency, accountability, responsibility, fairness and independence well. However, it was still found that .LAZ Dompet Ummat Kalbar did not use the services of an audit committee to audit its financial statements, had not informed the public of financial reports via the web and had not separated the duties and functions of the treasurer from the finance department